Civil Society and the State in Democratic East Asia : Between Entanglement and Contention in Post High Growth - Obinger, Julia; Grano, Simona Alba; Chiavacci, David (Protest and social movements., 2020)
This volume focuses on the new and diversifying interactions between civil society and the state in contemporary East Asia by including cases of entanglement and contention in the three fully consolidated democracies in the area: Japan, South Korea and Taiwan. The book argues that all three countries have reached a new era of post high-growth and mature democracy, leading to new social anxieties and increasing normative diversity, which have direct repercussions on the relationship between the state and civil society. It introduces a comparative perspective in identifying and discussing similarities and differences in East Asia based on in-depth case studies in the fields of environmental issues, national identities as well as neoliberalism and social inclusion that go beyond the classic dichotomy of state vs "liberal" civil society.